Analysis of PAHs contents and Health risk quantification in Telfairia occidentalis (fluted pumpkin) cultivated in the Crude oil Ecozone of the Niger-Delta - Ogwu, C.; Anani, O. A.; Ogana, J.; Agbe, E.; Okobia, U. B. (International Journal of Agricultural Technology, 2024)
The results of this study showed the various concentrations of pyrenes, chrysene, benzo[a]pyrene, benzo[a]anthracene, and benzo[b]fluoranthene (0.85±0.11, 2.87±0.12, 2.86±0.10, 2.84±0.11, and 2.78±0.13 µg/kg), respectively in the fluted pumpkin. The non-carcinogenic risks from the possible ingestion of PAH congeners in the fluted pumpkin sourced from different locations in the Niger Delta revealed the progression in values for Beneze (a) pyrene, Benzo (a) anthracene, and Benzo (b) fluoranthene as; 14.55 > 1.46 > 1.42 respectively of the TEFs (Toxicity equivalent factors). However, it was noticed that the mean across the studied sites was considerably higher than the threshold set for this study. The values of the chronic daily intake (CDI) for the PAHs investigated, fluctuated in the sites studied. The incremental cancer risk (ILCR) for this study showed that the concentrations of PAHs were also higher than the set threshold. The study concluded that T. occidentalis is contaminated by PAHs above the EU 1255/2020 stipulated level of 2.0 µg/kg for PAHs in vegetables and thus not good for human ingestion It is recommended that the oil companies operating in the Niger Delta adopt world-best practices in their operations, mitigation mechanisms of impacts should be adopted, remediation should be commissioned, and monitoring agencies should be mandated to increase surveillance on the operations of the oil exploration and exploitation companies operating in the Niger Delta